2017
DOI: 10.1136/bmjquality.u212185.w4870
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the uptake of electronic prescribing in primary care

Abstract: Electronic prescribing is a form of paperless prescribing that is reported to reduce prescription mistakes and increases the cost effectiveness of the process. In England, around 1.5 million prescriptions are generated in general practice daily. Thus by reducing costs and increasing efficiency of this system through electronic prescribing, costs can be driven down.In this Quality Improvement project, a GP practice in London with approximately 3000 patients on record was assessed for its electronic prescribing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Many studies have also shown that use of electronic prescribing systems in hospitals can help to reduce prescription errors. This may improve the quality of prescriptions as well as quality of care [26,27], but this requires sufficient funding and extensive training of doctors on the usage of electronic system. Factors such as age of doctors, years of experience, number of patients consulted per day, location of hospitals, and type of hospitals showed no significant association after adjusting for the confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have also shown that use of electronic prescribing systems in hospitals can help to reduce prescription errors. This may improve the quality of prescriptions as well as quality of care [26,27], but this requires sufficient funding and extensive training of doctors on the usage of electronic system. Factors such as age of doctors, years of experience, number of patients consulted per day, location of hospitals, and type of hospitals showed no significant association after adjusting for the confounders.…”
Section: Discussionmentioning
confidence: 99%
“…All medical students were able to identify a clinical problem and more than 90% have been able to apply robust QI methodologies with the aim to improve practice, gaining insights into problem‐solving strategies in their future careers. QIP report findings have also been disseminated through scholarly presentations and articles …”
Section: Discussionmentioning
confidence: 99%
“…QIP report findings have also been disseminated through scholarly presentations and articles. 10,11 Students wanted to choose a QIP to work on rather than be allocated one, and some suggested that they wanted to design their own project Challenges remain, however. Post-module evaluation has illustrated the impact of complete curriculum change on the students, particularly when a new module requires clinical teachers to deliver something novel.…”
Section: Discussionmentioning
confidence: 99%